Optimization of Anti-Nutritional Removal, Protein Extraction and Modification of Functional Properties of Cowpea (Vigna unguiculata L.) Protein with Sonication - Bambang Dwi Wijatniko; Agnes Murdiati; Chelsea Rie Eliza; Putri Tania Mofiagesa (Indonesian Food and Nutrition Progress, 2022)
Cowpea has high protein content which makes it is potential to be utilized as a protein isolate. However, cowpeas contain some anti-nutritional compounds which can lower the nutritional quality of the cowpeas. It is necessary to reduce the antinutritional contents from the cowpeas.The objective of this study was to investigate the optimum treatments for antinutritional removal and protein extraction to produce protein isolate. Removal of antinutritional was performed by a combination of soaking treatment with the duration of 24, 48, and 72 hours with 5% NaHCO3 solution and boiling for 0, 2.5, and 5 minutes. The protein extraction was conducted by adjusting the pH to various pH at 2, 4, 6, 8, 10, 11, and 12.Soaking of cowpeas seeds for 48 hours with 5% NaHCO3 significantly reduced HCN levels to 0.72 ppm, phytic acid of 9.62 mg / g, and trypsin inhibitor of 7.02 mg / g. The protein concentrate was obtained from protein extraction by using optimum pH at 12 while precipitation of protein by using pH 4 with protein concentration at 70.9%. Sonication with 80%-30 minutes indicated an increase in the water holding capacity, oil holding capacity, emulsion stability, foaming capacity, and stability rather than untreated